Viral-templated Palladium Nanocatalysts. - Yang, Cuixian. (2017)
Abstract: Despite recent progress on nanocatalysis, there exist several critical challenges in simple and readily controllable nanocatalyst synthesis including the unpredictable particle growth, deactivation of catalytic activity, cumbersome catalyst recovery and lack of in-situ reaction monitoring. In this dissertation, two novel approaches are presented for the fabrication of viral-templated palladium (Pd) nanocatalysts, and their catalytic activities for dichromate reduction reaction and Suzuki Coupling reaction were thoroughly studied. In the first approach, viral template based bottom-up assembly is employed for the Pd nanocatalyst synthesis in a chip-based format. Specifically, genetically displayed cysteine residues on each coat protein of Tobacco Mosaic Virus (TMV) templates provide precisely spaced thiol functionalities for readily controllable surface assembly and enhanced formation of catalytically active Pd nanoparticles. Catalysts with the chip-based format allow for simple separation and in-situ monitoring of the reaction extent. Thorough examination of synthesis-structure-activity relationship of Pd nanoparticles formed on surface-assembled viral templates shows that Pd nanoparticle size, catalyst loading density and catalytic activity of viral-templated Pd nanocatalysts can be readily controlled simply by tuning the synthesis conditions. The viral-templated Pd nanocatalysts with optimized synthesis conditions are shown to have higher catalytic activity per unit Pd mass than the commercial Pd/C catalysts. Furthermore, tunable and selective surface assembly of TMV biotemplates is exploited to control the loading density and location of Pd nanocatalysts on solid substrates via preferential electroless deposition. In addition, the catalytic activities of surface-assembled TMV-templated Pd nanocatalysts were also investigated for the ligand-free Suzuki Coupling reaction under mild reaction conditions. The chip-based format enables simple catalyst separation and reuse as well as facile product recovery. Reaction condition studies show that the solvent ratio played an important role in the selectivity of the Suzuki reaction, and that a higher water/acetonitrile ratio significantly facilitated the cross-coupling pathway. Meanwhile, in-depth characterizations including Atomic Force Microscopy (AFM), Grazing Incidence Small Angle X-ray Scattering (GISAXS), Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) and X-ray Photoelectron Spectroscopy (XPS) were carried out for these chip-based viral-templated Pd nanocatalysts. In the second approach, catalytically active TMV-templated Pd nanoparticles are encapsulated in readily exploited polymeric microparticle formats. Specifically, small (1~2 nm), uniform and highly crystalline palladium (Pd) nanoparticles are spontaneously formed along (TMV) biotemplates without external reducing agents. The as-prepared Pd-TMV complexes are integrated into the hybrid poly(ethylene glycol)(PEG)-based microparticles via replica molding (RM) technique in a simple, robust and highly reproducible manner. The Pd-TMV complex structure was characterized by Transmission Electron Microscopy (TEM). The hybrid Pd-TMV-PEG microparticles are examined to have high catalytic activity, recyclability and stability through dichromate reduction. Combined these findings represent a significant step toward simple, robust, scalable synthesis and fabrication of efficient biotemplate-supported Pd nanocatalysts in readily deployable polymeric formats with high capacity in a well-controlled manner. These two simple, robust and readily controllable approaches for the fabrication of viral-templated Pd nanocatalysts, in both chip-based and hydrogel-encapsulated formats, can be readily extended to a variety of other nano-bio hybrid material synthesis in other catalytic reaction systems.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Hyunmin Yi.; Committee: Jerry Meldon, Maria Flytzani-Stephanopoulos, Terry Haas, and Byeongdu Lee.; Keywords: Chemical engineering, Nanotechnology, and Materials Science.